IMPLEMENTATION OF CSR (CORPORATE SOCIAL RESPONSIBILITY) IN INCREASING THE IMAGE OF PT PERTAMINA - Lestari, Fina Tri; Suryatimur, Kartika Pradana (Transpublika Publisher, 2023)
This research aims to find out the implementation of the CSR (Corporate Social Responsibility) program carried out by PT. Pertamina (Company) in order to improve the company's image. The research strategy employed is qualitative in nature. This research was not conducted to test the hypothesis between the two research variables, but rather to describe the extent to which CSR programs implemented by PT. Pertamina can contribute to the enhancement of the company's image. This study's data is derived from the 2021 annual report of PT. Pertamina, which was obtained from IDX, as well as articles and other documents relevant to the research topics. On the basis of the research findings, it can be concluded that PT. Pertamina has implemented its CSR program in accordance with its vision and mission. The implementation of CSR by PT. Pertamina has a significant impact on the enhancement of the company's image, reputation, and credibility. In this case, what PT. Pertamina has to do is improve the implementation of the programs being carried out so that it can expand the target development of the CSR programs being carried out and more people will benefit, re-mapping of the community's economic conditions before and after program implementation, and the need for regular monitoring and evaluation processes to obtain feedback in an effort to increase program benefits in the future.